Enrichment of table eggs with lutein - Kralik, Gordana (Array, 2020)
For the enrichment of eggs with lutein, a marigold flower extract – MFE (Tagetes erecta L.) was used. The two groups of laying hens were involved in the study – the control group (C) and the experimental group (E), respectively. The laying hens of the control group were fed by the lutein‐free mixture, while the laying hens’ E group consumed the mixture with the 3 g/kg of lutein. The laying hens’ feeding lasted for 31 days, after which the quality of eggs (i.e., the shape index, egg weight and the egg main parts, shell strength and thickness, Haugh units – HU, egg white height, egg yolk color, egg white pH, and the egg yolk pH), as well as the lutein content and Thiobarbituric Acid Reactive Substances (TBARS) values in egg yolks, were determined. The study results have demonstrated that the added MFE exerted an effect of thickness, weight, and eggshell proportion reduction (P<0.001), as well as of the shell strength reduction (P=0.014). It has also reduced the HU value (P=0.039) and has increased the egg white content, egg yolk color, and the egg yolks’ lutein content (P<0.001). A statistically significant difference in TBARS values was found between the fresh and the stored eggs in group C, as well as between the C and E groups in the fresh eggs (P<0.05). Our results indicate that MFE is suitable for the enrichment of table eggs with lutein.